Enhanced bioelectrochemical performance caused by porous metal-organic framework MIL-53(Fe) as the catalyst in microbial fuel cells. (December 2020) - Wang, Hongying; Jiang, Liting; Chen, Junfeng; Fu, Mengyu; Diao, Zhongyu; Liu, Huanhuan; Guo, Huamin
Graphical abstract: Highlights: Fe-based metal organic framework (MIL-53(Fe)) was synthesized. MIL-53 (Fe) showed remarkable stability and durability in MFC cathode. MIL-53 (Fe) improved oxygen reduction reaction (ORR) and power generation capacity. Max power density of microbial fuel cell with MIL-53 (Fe) was 397 ± 6.3 mW/m 2 . Abstract: To enhance the oxygen reduction reaction (ORR) activity and power generation capacity of a microbial fuel cell (MFC), MIL-53(Fe) (Fe-based Materials of Institute Lavoisier) as the electrochemical catalyst was synthesized using the hydrothermal method. The catalytic structure and morphology of all materials were comprehensively characterized by Fourier Transform infrared spectrometer (FTIR), X-ray diffraction (XRD), scanning electron microscope (SEM) and energy dispersive spectrometer (EDS). The results show that there were many nanopores on MIL-53(Fe), which improved the electrocatalytic activity. The MIL-53(Fe)-modified air cathode MFC had a voltage output of approximately 0.37 V and maintained that output for one week. The maximum power density was 397 ± 6.3 mW/m 2 . MIL-53(Fe) was an excellent electrochemical catalyst, significantly enhancing the catalytic oxygen reduction ability and promoting the power output of the MFC. This study provides a method to apply MIL-53(Fe) materials in microbial fuel cells.